Survey of consent practices in cluster randomized trials: Improvements are needed in ethical conduct and reporting. (February 2014) - Taljaard, Monica; Chaudhry, Shazia H; Brehaut, Jamie C; Weijer, Charles; Boruch, Robert; Donner, Allan; Eccles, Martin P; McRae, Andrew D; Saginur, Raphael; Zwarenstein, Merrick; Grimshaw, Jeremy M
Background: Informed consent procedures in cluster randomized trials (CRTs) are considerably more complicated than in individually randomized trials. In a CRT, the units of randomization, intervention, and observation may differ in a single trial; there can be multiple levels of participants (individual and cluster level); consent may be required separately for intervention and data collection; and there may be practical constraints to seeking informed consent, for example, due to cluster-level interventions or the sheer size of clusters. Purpose: We aimed to document consent practices at individual and cluster levels, assess the adequacy of reporting consent in trial publications, and assess associations with two trial characteristics that may influence consent requirements in CRTs: presence or absence of study interventions and presence or absence of data collection procedures at individual and cluster levels. Methods: We reviewed a random sample of 300 CRTs published during 2000–2008. We sent survey questionnaires to 285 unique authors of these trials to gather detailed information about consent procedures used in each trial. Results: In all, 182 authors (64%) responded. Overall, 93% (95% confidence interval (CI): 88.8%−96.6%) indicated that participant consent had been sought for some aspects of the study. Consent was less frequently sought for a study intervention (70% of respondents) than for data collection (88%). More than half of the respondents (52%) indicated that consent had been sought at both cluster and individual levels. There was strong evidence for under-reporting of consent in trial publications: only 63% of all trial publications reported that informed consent had been sought for some aspect of the study. The odds ratios (ORs) summarizing the association of the two trial characteristics with cluster-level participant consent were weak (OR = 1.17, p = 0.70 for presence of cluster-level study intervention and OR = 1.54, p = 0.29 for data collection); on the other hand, the ORs summarizing the associations with individual-level consent were strong (OR = 6.2, p < 0.0001 for presence of individual-level intervention and OR = 14.7, p < 0.0001 for data collection). Limitations: In all, 36% of authors did not respond to the survey; to the extent that consent practices in their trials were different than in respondents' trials, our results may be biased. Conclusions: There is a need for improvements in research practices in CRTs as well as their reporting. There may be a lack of clarity about consent requirements at the cluster level in particular. With the publication of the Ottawa Statement on the Ethical Design and Conduct of Cluster Randomized Trials, researchers and research ethics committees now have access to comprehensive ethics guidelines specific to CRTs.